The Validity of the Holtzman Inkblot Technique: New Indices - Dawe, James; Hawkins II, Raymond C.; Lauriola, Marco; Leichsenring, Falk; Pezzuti, Lina (Frontiers in Psychology, 2021)
Objective: The present study examines the validity of eleven new Holtzman Inkblot Technique indices. These were chosen from Exner’s Comprehensive System (RCS) indices using two criteria: first, they had to be valid according to Mihura et al.'s (2013) meta-analysis, and second, they must be computed using the HIT standard scoring system. Methods: Both techniques were administrated to a sample of 139 subjects (63 males and 76 females) from the general population. The validity of the new indices was studied through Pearson correlations (r) with the corresponding RCS indices. Results: nine of the eleven new indices (R-HIT, L-HIT, M-HIT, m-HIT, C’-HIT, Blends-HIT, PureH-HIT, and DQ+HIT, and X-%-HIT) showed significant correlations with Rorschach scales, confirming our hypotheses. The correlations ranged from a minimum of .144 to a maximum of .414. Conclusions: The results provide support for the validity of the new HIT indices and have important implications for both clinical and research fields.